2022-LBA-746-ESGO Implementation of a comprehensive cancer genome profiling programme into clinical practice: an italian experience in a referral centre for gynecological cancers. (27th October 2022) - Nero, Camilla; Pelligra, Silvia; Duranti, Simona; Giacomini, Flavia; Camarda, Floriana; Giudice, Elena; Piermattei, Alessia; Sillano, Francesca; Minucci, Angelo; de Bonis, Maria; Raspaglio, Giuseppina; Giacò, Luciano; et al.
Abstract : Introduction: The implementation of cancer molecular characterization in clinical practice has improved prognostic re- definition extending the eligibility to a continuous increasing number of targeted treatments. A molecular based primary tumor agnostic approach, could satisfy this purpose. Although in 2020 the European Society of Medical Oncology recommended comprehensive genomic profiling (CGP) implementation at least in academic centers many challenges have to be acknowledged. Methods: In the present monocentric interventional prospective study, ten cancer types including ovarian and endometrial cancer treated at our Institution from January 2022, were identified and profiled using a FPG500 molecular platform. An analysis was designed to evaluate the feasibility of CGP from Formalin- Fixed Paraffin- Embedded specimens, turnaround times, presence of targetable alteration as well as a description of the mutational landscape, enrollment rate in clinical trials, indications for referral to genetic counseling. Molecular features were further correlated with available clinico-pathological variables for each disease type. Results: Out of 188 women, the feasibility of CGP was 98%, with a mean turnaround time of 39 days. 33.5% of the population was referred to genetic counselling. Most significant findings are reported in Table 1 . Conclusions: Regarding ovarian cancer, as expected, endometrioid and clear cell histotypes had different mutational profiles compared to serous ones (KRAS, ERBB2, FGF7, LRP1B, MDC1 and SPEN vs BRCA 1, FGF2, FGF7, FGFR3, TP53 respectively) with a minimum incidence of mutations. Regarding endometrial cancer, no difference was observed in clinical features for patients with TMB>10. No difference was observed between patients younger or older than 50 years. A TMB>10 was found in 35% of patients with 475 altered genes (mean=28) the most frequent being PTEN (82%), ARID1A (71%), and PIK3CA (65%).